The modernization of civil rotorcraft certification system in Korea - Kim, Y.H.; Yoon, H.K.; Chung, H,G.; Oh, M. (My University, 2020)
The ROK MND have successfully developed two types of military helicopters in last two decades, in cooperation with Airbus Helicopters. Though these rotorcrafts were basically developed to conduct various tactical duties, their civil derivatives were also developed for cost-effective operation. Since it is apparent that these rotorcrafts will apply for their STC and RTC respectively, the demand to harmonize the civilian rotorcraft certification system was clearly recognized in ROK. Therefore, the KIAST (Korea Institute of Aviation Safety Technology) have been conducting a project since 2017, to improve the civil rotorcraft certification system. This document is providing the general overview of this effort.